Initial experience with robotic navigation for catheter ablation of paroxysmal and persistent atrial fibrillation - Thomas, Dierk; Scholz, Eberhard P.; Schweizer, Patrick Alexander; Katus, Hugo; Becker, Rüdiger (Journal of electrocardiology, 2012)
Background and Purpose: Remote robotic navigation (RRN) technology has been developed to facilitate catheter ablation of symptomatic atrial fibrillation (AF). Here, we assess procedural parameters of AF ablation obtained during initial use of RRN compared with a control group treated with a manual ablation approach. Methods: Consecutive patients with symptomatic paroxysmal or persistent AF were subjected to radiofrequency catheter ablation with RRN (Sensei X [Hansen Medical, Mountain View, CA]; n = 25; mean age, 60 ± 2.3 years) or using the standard manual technique (n = 61; mean age, 62 ± 1.4 years). A circumferential pulmonary vein isolation approach guided by 3-dimensional electroanatomical mapping was followed. Results: Remote robotic navigation was associated with reduction of overall fluoroscopy time by 26%. In a case-control subgroup analysis comparing 25 patients with similar clinical characteristics from each group, mean fluoroscopy time was reduced by 22%. Acute isolation of pulmonary veins was achieved in 97% (RRN) and 96% (conventional ablation), respectively. Ablation times and frequency of adverse events were not significantly different among study groups. Conclusions: The early use of RRN resulted in a significant reduction of overall fluoroscopy time and was equally effective and safe compared with manual catheter ablation.
Gesehen am 02.05.2018
Article was published online on June 29, 2011